Functional dyspepsia symptom resolution after Helicobacter pylori eradication with two different regimens - Sarikaya, Murat; Dogan, Zeynal; Ergül, Bilal; Filik, Levent (Gastroenterology Review/Przegląd Gastroenterologiczny, 2014)
Introduction : Functional dyspepsia (FD), a common functional gastrointestinal disorder, has a complex underlying pathophysiological mechanism that involves changes in gastric motility, visceral hypersensitivity, genetic susceptibility, psychosocial factors and Helicobacter pylori infection. Although there are several H. pylori eradication treatments, there is not enough data that compare these different eradication treatments for FD symptom resolution. Most previous studies have focused on the eradication rates of H. pylori rather than symptom relief in FD. Aim : In this regard, we aimed to clarify if there is any difference between standard triple therapy and sequential therapy for symptom resolution of FD patients with H. pylori , using a validated health quality index. Material and methods : A total of 194 patients were included in this study. The patients were randomly assigned to receive standard triple therapy (omeprazole, amoxicilline and clarithromycin for 14 days) or sequential therapy (omeprazole plus amoxicilline for 7 days and omeprazole twice daily, metronidazole and clarithromycin for a subsequent 7 days) by a blind physician for H. pylori status. Outcome measures were based on symptomatic improvement at 12 months using a validated measure of subjective well-being (Gastrointestinal Symptom Rating Scale – GSRS). Results : We observed significant symptom resolution at 12 months in both treatment groups. On the other hand, there was no difference between the sequential or standard triple therapy groups regarding the alleviation of symptoms. Conclusions : No difference for symptom relief exists between sequential and triple therapy in patients with FD.